MENINGKATKAN HASIL BELAJAR SISWA TERHADAP PEMBELAJARAN TARI MELALUI MEDIA AUDIOVISUAL DI SMA NEGERI 12 PADANG - Raju Gunawan; Indrayuda Indrayuda; Fuji Astuti (SENDRATASIK UNP, 2018)
Abstract This article aims to describe and express the improvement of male student study result of dance at XI IPS 1 class in SMA Negeri 12 Padang by using Audiovisual Medium. Kind of the study was a study of class action (PTK). Instrument of the study was a researcher and assisted by observer namely colleague and it was also supported by other tools such as laptop, speaker, music, video and audiovisual (VCD). Technique of data collection was done by using library research, observation, action and taking documentation. The result of study showed that the use of audiovisual medium in art and culture learning especially in dancing at XI IPS 1 class in SMA Negeri 12 Padang could improve the study result and it was able to allow students to involve in learning of the dance subject directly. In the first of cognitive meeting cycle, the avarage score was 56,76%, meanwhile in the first of psychoomotor meeting cycle,  the avarage score was 59,12% and in the second of cognitive meeting cycle, the avarage score was 83,82%, meanwhile in the second of psychoomotor meeting cycle, the avarage score was pertemuan 83,24%. So, it could be seen that there was improvement of the study result of dance learning by using audiovisual medium and the achieved target had been suceed. Keywords: Improvement, Study Result, Audiovisual Medium, Dance